The Beltrami equations and prime ends - Gutlyanskii, V.Y.; Ryazanov, V.I.; Yakubov, E. (Український математичний вісник, 2015)
We first study the boundary behavior of ring Q-homeomorphisms in terms of Carath´eodory’s prime ends and then give criteria to the solvability of the Dirichlet problem for the degenerate Beltrami equation ∂f = μ∂f in arbitrary bounded finitely connected domains D of the complex plane C: